The importance of socialization in achieving universal health coverage: case study of Jaminan Kesehatan Nasional (JKN) implementation in two different region in Central Java province - Ema Nur Fitriana; Ari Natalia Probandari; Eti Poncorini Pamungkasari; Tonang Dwi Ardyanto; Rizky Amalia Puspitaningrum (Faculty of Medicine, Universitas Islam Indonesia, 2019)
Background: Jaminan Kesehatan Nasional (JKN) is Indonesia's health policy to achieve universal health coverage (UHC). Towards 2019, not all regions have succeeded in achieving UHC. One of the reasons is the uneven distribution of information regarding JKN policies. Socialization is needed so that the JKN policy is understood by the people of Indonesia. Objective: This research was design to describe the importance of JKN policy socialization to reach UHC. Methods: Qualitative research was conducted in September 2018- February 2019 in two districts in Central Java, that were the district that had reached UHC and districts that had not yet reached UHC. The informants consisted of leaders of regional organizations and also the community. The researcher conducted an interactive model analysis on the interview transcript. Results: In districts that had reached UHC, socialization was conducted directly and indirectly through the government, community cadres and BPJS cadres. The district government provided support by issuing circulars letters. The district socialization effectively increases JKN participants. Meanwhile, in districts that had not yet reached UHC, there was found differences between community and the government. The government said that they had conducted effective socialization. But the community said that the information provided has not been effective and there is no detailed information about JKN.Conclusion: An effective socialization of JKN policies is needed to increase the understanding and awareness of the community to achieve UHC.